2015
DOI: 10.1002/ange.201502949
|View full text |Cite
|
Sign up to set email alerts
|

A Triphenylamine with Two Phenoxy Radicals Having Unusual Bonding Patterns and a Closed‐Shell Electronic State

Abstract: Scheme 1. a) Structures of the galvinoxyl radical. Structures of 1 drawn as abiradical (b) and aclosed-shell form (c).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[1][2][3] Recently,w e have reported structural and electronic properties of at riarylamine having two 2,6-di-tert-butylphenoxy radical on the central nitrogen atom (1). [4] Our study revealed that 1 had extended quinoids tructure resulting from the stronga ntiferromagnetic coupling between two phenoxy radicals through the central amino nitrogen atom. The two CÀNb onds between the central nitrogen atom and the phenoxy groups explicitly had multiple bond characterl eadingt oi ts closed-shell electronic nature in contrastt ot he other phenoxy radical-based diradicals.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…[1][2][3] Recently,w e have reported structural and electronic properties of at riarylamine having two 2,6-di-tert-butylphenoxy radical on the central nitrogen atom (1). [4] Our study revealed that 1 had extended quinoids tructure resulting from the stronga ntiferromagnetic coupling between two phenoxy radicals through the central amino nitrogen atom. The two CÀNb onds between the central nitrogen atom and the phenoxy groups explicitly had multiple bond characterl eadingt oi ts closed-shell electronic nature in contrastt ot he other phenoxy radical-based diradicals.…”
mentioning
confidence: 66%
“…[4] The obtained biphenols were oxidized with lead (IV) oxide in dichloromethane at room temperature. The biphenol precursors (3a-d)w ere obtained by the palladium-catalyzed Buchwald-Hartwig reaction between the corresponding aniline derivatives (Ar-NH 2 )a nd methoxymethyl (MOM)-protected 2,6-di-phenyl-4-bromophenol, followedb yt he deprotection of the MOM groups by acidification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…288-332,February 11, 2021 303 Review expected to distribute at the outer centers of the trimethylenemethane groups, whereas their charge orders were rather negligible according to the ESR and EN-DOR, as well as the quantum chemical calculations. Sakamaki et al75 reported a triphenylamine derivative 41 with two appended phenoxyl radicals. They experimentally determined that the molecule 41 possessed a closed-shell electronic structure and the C-N bonds had a multiple-bond character due to the robust delocalization.…”
mentioning
confidence: 99%